Bone morphogenetic protein‐9 induces epithelial to mesenchymal transition in hepatocellular carcinoma cells. Issue 3 (13th February 2013) - Li, Qi; Gu, Xing; Weng, Honglei; Ghafoory, Shahrouz; Liu, Yan; Feng, Teng; Dzieran, Johanna; Li, Li; IIkavets, Iryna; de, Marianna Kruithof‐; Munker, Stefan; Marx, Alexander; et al.
<x xml:space="preserve">Abstract</x> Epithelial‐mesenchymal transition (EMT) is an important mechanism to initiate cancer invasion and metastasis. Bone morphogenetic protein (BMP)‐9 is a member of the transforming growth factor (TGF)‐β superfamily. It has been suggested to play a role in cancer development in some non‐hepatic tumors. In the present study, two hepatocellular carcinoma (HCC) lines, HLE and HepG2, were treated with BMP‐9 in vitro, and phenotypic changes and cell motility were analyzed. In situ hybridization (ISH) and immunohistochemical analyses were performed with human HCC tissue samples in order to assess expression levels of BMP‐9. In vivo, BMP‐9 protein and mRNA were expressed in all the tested patients to diverse degrees. At the protein level, mildly positive (1 + ) BMP‐9 staining could be observed in 25/41 (61%), and moderately to strongly positive (2 + ) in 16/41 (39%) of the patients. In 27/41 (65%) patients, the BMP‐9 protein expression level was consistent with the mRNA expression level as measured by ISH. In those patients with 2 + protein level, nuclear pSmad1 expression in cancer cells was also significantly increased. Expression of BMP‐9 was positively related to nuclear Snail expression and reversely correlated to cell surface E‐cadherin expression, although this did not reach statistical significance. Expression levels of BMP‐9 were significantly associated with the T stages of the investigated tumors and high levels of BMP‐9 were detected by immunofluorescence especially at the tumor borders in samples from an HCC mouse model. In vitro, BMP‐9 treatment caused a reduction of E‐cadherin and ZO‐1 and an induction of Vimentin and Snail expression. Furthermore, cell migration was enhanced by BMP‐9 in both HCC cell lines. These results imply that EMT induced by BMP‐9 is related to invasiveness of HCC.